Comparative randomized controlled clinical trial of diathermy versus scalpel incision in midline laparotomy - Vadodariya, Bhavin P.; Shah, Nimish J.; Patel, Mrudul (International Surgery Journal, 2018)
Background: Laparotomy incisions have traditionally been made using a scalpel. Diathermy, a latest technique, is thought to increase the risk of infection, impair healing and decrease cosmesis. Recent studies suggest that diathermy may offer likely advantages with respect to blood loss, incision time and postoperative pain. The aim of this study was to compare the efficacy and safety of surgical diathermy incisions versus conventional scalpel incisions for midline laparotomy in our hospital with an aim to evaluate diathermy as an operational alternative to scalpel incision. Methods: This was a prospective randomized clinical study which was conducted in the surgical wards of Medical College & SSG hospital, Vadodara, between December 2013 and December 2014. Patients were randomly assigned to two groups i.e. Group A (scalpel group) and Group B (diathermy group). Results: A total of 148 patients were enrolled in the study. Of these, 74 patients were randomized to Group A (scalpel group) and 74 patients to Group B (diathermy group). The two groups did not vary significantly in relation to age and sex (p>0.001). Laparotomy skin incisions using diathermy were significantly quicker than scalpel incisions (p=0.624). There was significantly less blood loss in the diathermy group compared with the scalpel group (P=0.15). The mean visual analogue scale was significantly reduced more in the diathermy group than in scalpel group patients on postoperative day 1 (p=0.81), day 3 (p=0.71) and day 5 (p=0.79) respectively. Postoperative complication rates did not differ significantly between the scalpel and diathermy groups (p=0.624). Conclusions: We concluded that diathermy incision in midline laparotomy has significant advantages compared with the scalpel because of reduced incision time, less blood loss, reduced early postoperative pain and postoperative wound infection.